2003
DOI: 10.1103/physrevlett.91.170601
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Renormalization Group for Bosonic Systems and Application to the Sub-Ohmic Spin-Boson Model

Abstract: We describe the generalization of Wilson's Numerical Renormalization Group method to quantum impurity models with a bosonic bath, providing a general non-perturbative approach to bosonic impurity models which can access exponentially small energies and temperatures. As an application, we consider the spin-boson model, describing a two-level system coupled to a bosonic bath with power-law spectral density, J(ω) ∝ ω s . We find clear evidence for a line of continuous quantum phase transitions for subohmic bath e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
449
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(479 citation statements)
references
References 21 publications
(59 reference statements)
26
449
4
Order By: Relevance
“…DMRG was a substantial improvement [25] on the older numerical renormalization group (NRG), which had only a poor reputation in dealing with long-range interactions between fermions [31,32], but we found it useful for bosonic systems (see also Ref. [33]). …”
Section: Introductionmentioning
confidence: 99%
“…DMRG was a substantial improvement [25] on the older numerical renormalization group (NRG), which had only a poor reputation in dealing with long-range interactions between fermions [31,32], but we found it useful for bosonic systems (see also Ref. [33]). …”
Section: Introductionmentioning
confidence: 99%
“…This conclusion was based on the non-interacting-blip approximation 1,7 which fails in the weak-coupling limit to the bath. More recently, several works 5,8,9 addressed the problem of the sub-Ohmic spin-boson model and found that coherent phases can exist for sufficiently weak coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate more thoroughly the temperature and frequency dependences of the local spin susceptibility of the spin-boson model, as calculated using the bosonic NRG approach. 11,12 The subleading term in the temperature dependence at ω = 0 is shown to be described by an exponent x 2 that depends on ǫ and exceeds 1 2 , contradicting a central assumption of Ref. 18.…”
mentioning
confidence: 89%
“…13 assumed the the classical spin chain faithfully represents the spin-boson model. Correspondingly, it interpreted the Monte-Carlo result as demonstrating a fundamental error in the NRG results 9,11,12 for the sub-ohmic spin-boson model. It was further suggested in Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation